Sherlock Holmes - Ritchie, Guy; Downey, Robert, 1965-; Law, Jude, 1972-; McAdams, Rachel, 1978-; Doyle, Arthur Conan, 1859-1930 (Burbank, CA : Warner Home Video, 2010)
Holmes and his assistant Dr. Watson are on the trail of Lord Blackwood, a serial killer they captured and saw executed, but has apparently risen from the grave to resume his killing spree.
Based on the characters created by Arthur Conan Doyle.
Originally released as a motion picture in 2009.
Features: Sherlock Holmes reinvented.
Robert Downey Jr., Jude Law, Rachel McAdams, Mark Strong, Eddie Marsan.
MPAA rating: PG-13.
DVD, Dolby digital 5.1.
Keywords: Doyle, Arthur Conan, -- 1859-1930 -- Film and video adaptations; Great Britain. -- Metropolitan Police Office. -- Criminal Investigation Dept -- Drama; Holmes, Sherlock (Fictitious character) -- Drama; Watson, John H. (Fictitious character) -- Drama; Murder -- Investigation -- England -- Drama; Criminal investigation -- England -- Drama; Detective and mystery films; Action and adventure films; Video recordings for the hearing impaired; Fiction films; Based on the book; Feature films; Detective films; Mystery films